Integrating motivation in instructional design - Wong, Shu Ling; Wong, Su Luan (Universiti Putra Malaysia Press, 2017)
This paper explores the construct of motivation from the perspective of the instructional designer or teacher. It describes the motivation to learn in the context of intrinsic motivation, Expectancy-value Theory, Self-efficacy Theory, and Attribution Theory. The ARCS motivational model is examined in detail before discussing how motivation can be integrated in instructional design to enhance learning. This paper also explicates Cheng and Yeh’s (2009) framework in the context of classroom learning.